Solar cell and preparation method thereof

By using urea-based compounds to form an interface modification layer in perovskite solar cells, the problems of self-assembled single-layer coverage are solved, and the carrier transmission performance is significantly improved, thereby improving the overall solar cell performance.

CN119136616APending Publication Date: 2024-12-13TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411234755.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the problems of self-assembled single-molecule layer coverage in perovskite solar cells lead to poor carrier transport performance, and existing solutions such as additives and surface treatment effects are not obvious or unsatisfactory. .

Method used

The urea-based compound is dissolved to form an interface modification precursor solution, and the interface modification layer is formed on the self-assembled single molecule layer by spin coating, and the perovskite light absorption layer, electron transport layer, hole barrier layer and Metal electrodes, using specific solvents and annealing conditions to improve carrier transport performance.

Benefits of technology

It effectively improves the perovskite film coverage unevenness, improves carrier transmission performance, and improves the overall performance of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136616A_ABST
    Figure CN119136616A_ABST
Patent Text Reader

Abstract

The invention provides a solar cell and a preparation method thereof, and the preparation method of the solar cell comprises the following steps: dissolving a ureido compound in a solvent to obtain an interface modification precursor solution; a self-assembly monomolecular layer is spin-coated with the interface modification precursor solution, so that an interface modification layer for improving the carrier transport performance of the self-assembly monomolecular layer is formed on the self-assembly monomolecular layer, the hole transport layer is the self-assembly monomolecular layer, and therefore the carrier transport performance at an interface is improved; and sequentially preparing a perovskite light absorption layer, an electron transport layer, a hole blocking layer and a metal electrode on the interface modification layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a solar cell and a method for preparing the solar cell. Background Art

[0002] Perovskite solar cells (PSCs) have achieved record power conversion efficiencies (PCEs) of more than 26%. Based on the vision of large-scale use, operational stability and mechanical reliability have become key issues in the field of perovskite solar cells. Stronger mechanical bonding between various interfaces in PSCs can reduce the propensity for defect nucleation (pores, cracks) during operation and enhance the resistance to the expansion of any such defects at these interfaces, thereby preventing delamination. In the field of tandem photovoltaic (PV) applications, inverted pin PSCs have higher efficiencies and are generally easier to manufacture and have better stability compared to nip structures. However, the important issue of interfacial mechanical adhesion in pin PSCs has not been fully addressed.

[0003] In trans-PSCs, carbazole-based phosphonic acids form monolayers or near-monolayers (often referred to as self-assembled monolayers or SAMs) to replace conventional (HTLs) such as {2-(9H-carbazole-9-yl)ethylphosphonic acid (2PACz) and {4-(3,6-dimethyl-9H-carbazole-9-yl)butylphosphonic acid (Me-4PACz). These materials have excellent electron blocking and hole selection properties due to the relatively low ionization energy and low electron affinity of carbazole. In addition, the phosphonic acid groups strongly bind to the indium tin oxide (ITO) transparent conducting oxide (TCO) surface through a combination of double and triple bonds. Studies have shown that 2PACz and Me-4PACz SAMs in PSCs provide favorable dipole states that help to efficiently extract photocarriers. However, current self-assembled monolayers have defects, such as the possibility of obtaining incomplete coverage and reduced wettability of perovskite precursor solutions.

[0004] In the prior art, co-assembly with another SAM, the use of additives, ITO surface treatment and oxide layer are usually used to solve the coverage problem. The wettability problem is solved by introducing additives into the molecular solution forming the SAM, using a porous aluminum oxide layer on the ITO, etc. However, the effect of additives in improving wettability in the existing methods is not obvious, and it is more sensitive to concentration. Some additives that improve wettability will reduce the ability of the SAM material to extract holes, and the effect of surface treatment using equipment such as ozone is poor.

[0005] In order to overcome the above-mentioned defects of the prior art, there is an urgent need in the art for a solar cell technology to improve the unfavorable phenomenon of uneven coverage of perovskite film due to the hydrophobicity of SAM materials, thereby improving the carrier transport performance at the interface and improving the performance of the device. Summary of the invention

[0006] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or decisive elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.

[0007] In order to overcome the above-mentioned defects of the prior art, the present invention provides a solar cell and a method for preparing a solar cell, which are used to improve the unfavorable phenomenon of uneven coverage of perovskite film due to the hydrophobicity of SAM material, thereby improving the carrier transport performance at the interface, thereby improving the performance of the device.

[0008] Specifically, the method for preparing a solar cell provided according to the first aspect of the present invention comprises the following steps: dissolving a urea-based compound in a solvent to obtain an interface modification precursor solution; and spin-coating the interface modification precursor solution on a self-assembled monolayer to form an interface modification layer on the self-assembled monolayer to improve its carrier transport performance; and sequentially preparing a perovskite light absorption layer, an electron transport layer, a hole blocking layer and a metal electrode on the interface modification layer.

[0009] Furthermore, in some embodiments of the present invention, the solvent is at least one of ethanol and isopropanol, the urea-based compound includes hydroxyurea, and its concentration is 1 mg / ml to 1.8 mg / ml, and / or the annealing temperature for preparing the interface modification layer is 80°C to 100°C, and its annealing time is 10min to 15min.

[0010] Furthermore, in some embodiments of the present invention, the interface modification precursor solution is spin-coated on the self-assembled monolayer based on a one-step spin coating method, wherein the spin coating speed is 1500 rpm to 3000 rpm and the spin coating time is 15 s to 30 s.

[0011] Furthermore, in some embodiments of the present invention, the material of the self-assembled monolayer includes at least one of 2PACZ, 4PACZ and Me-4PACZ.

[0012] Further, in some embodiments of the present invention, the step of preparing the self-assembled monolayer includes: spin coating the self-assembled monolayer material with a concentration of 0.3 mg / ml to 1 mg / ml on the substrate. The spin coating speed is 1500 rpm to 3000 rpm, the spin coating time is 15s to 30s, and the annealing temperature for preparing the self-assembled monolayer is 80°C to 100°C, and the annealing time is 10min to 20min.

[0013] Furthermore, in some embodiments of the present invention, the substrate is FTO glass, ITO glass or a flexible ITO conductive substrate. Before preparing the self-assembled monolayer, the preparation method also includes the following steps: placing the substrate in an ultrasonic cleaning device, and cleaning the substrate with detergent-free water, deionized water, and ethanol in sequence, wherein each step takes 10 minutes to 20 minutes; and performing ultraviolet ozone cleaning treatment on the substrate using an ultraviolet ozone cleaning device, wherein the ultraviolet ozone cleaning treatment takes 10 minutes to 20 minutes.

[0014] Furthermore, in some embodiments of the present invention, after forming the interface modification layer, the preparation method also includes the following steps: dissolving a perovskite light absorbing layer precursor in an organic solvent to obtain a perovskite precursor solution; spin coating the perovskite precursor solution on the surface of the interface modification layer to prepare the perovskite light absorbing layer, wherein the annealing temperature for preparing the perovskite light absorbing layer is 100°C to 150°C, and the annealing time is 15min to 35min; and sequentially depositing the electron transport layer, the hole blocking layer and the metal electrode on the surface of the perovskite light absorbing layer.

[0015] Further, in some embodiments of the present invention, the perovskite precursor includes at least one of FAMAPbI, FACsPbI, and FAMACsPbI. The organic solvent is a mixture of DMF and DMSO in a volume ratio of 3:1 to 5:1, or the organic solvent is a mixture of GBL and NMP in a volume ratio of 3:1 to 5:1.

[0016] Furthermore, in some embodiments of the present invention, the material of the electron transport layer is C 60 Or PCBM, the material of the hole blocking layer is BCP, and the thickness of the deposited metal electrode is 60nm-80nm.

[0017] In addition, the solar cell provided according to the second aspect of the present invention is prepared by the method for preparing a solar cell as described in any one of the first aspect of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above features and advantages of the present invention can be better understood after reading the detailed description of the embodiments of the present disclosure in conjunction with the following drawings. In the drawings, the components are not necessarily drawn to scale, and components with similar related properties or features may have the same or similar reference numerals.

[0019] Figure 1 A schematic structural diagram of a solar cell provided according to some embodiments of the present invention is shown.

[0020] Figure 2 A schematic flow chart of a method for preparing a solar cell according to some embodiments of the present invention is shown. DETAILED DESCRIPTION

[0021] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may be extended based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description.

[0022] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0023] In addition, the terms "upper", "lower", "left", "right", "top", "bottom", "horizontal" and "vertical" used in the following description should be understood as the directions shown in the paragraph and the related drawings. Such relative terms are only used for the convenience of description and do not mean that the device described therein must be manufactured or operated in a specific direction, and therefore should not be understood as limiting the present invention.

[0024] It is understood that although the terms "first", "second", "third", etc. may be used herein to describe various components, regions, layers and / or parts, these components, regions, layers and / or parts should not be limited by these terms, and these terms are only used to distinguish different components, regions, layers and / or parts. Therefore, the first component, region, layer and / or part discussed below may be referred to as a second component, region, layer and / or part without departing from some embodiments of the present invention.

[0025] As mentioned above, the problem of coverage is usually solved by co-assembly with another SAM, using additives, using ITO surface treatment and using an oxide layer. The wettability problem is solved by introducing additives into the molecular solution forming the SAM, using a porous aluminum oxide layer on the ITO, etc. However, the effect of additives in improving wettability in the existing methods is not obvious, and it is more sensitive to concentration. Some additives that improve wettability will reduce the ability of the SAM material to extract holes, and the effect of surface treatment using equipment such as ozone is poor.

[0026] In order to overcome the above-mentioned defects of the prior art, the present invention provides a solar cell and a method for preparing a solar cell, which are used to improve the unfavorable phenomenon of uneven coverage of perovskite film due to the hydrophobicity of SAM material, thereby improving the carrier transport performance at the interface, thereby improving the performance of the device.

[0027] Please refer to Figure 1 , Figure 1 A schematic structural diagram of a solar cell provided according to some embodiments of the present invention is shown.

[0028] like Figure 1 As shown, the solar cell includes, from bottom to top, a substrate layer, a hole transport layer, an interface modification layer, a perovskite light absorption layer, an electron transport layer, a hole blocking layer, and an electrode. Here, the substrate layer can be a substrate layer of a stacked cell or a substrate layer of a single junction cell. The hole transport layer is a self-assembled monolayer, thereby improving the carrier transport performance at the interface.

[0029] The following will describe the preparation principle of the above solar cell in combination with some embodiments of the preparation method of solar cells. Those skilled in the art will understand that the preparation method of the solar cell is only some non-limiting implementation methods provided by the present invention, which is intended to clearly demonstrate the main concept of the invention and provide some specific solutions that are convenient for the public to implement, rather than to limit the entire structure and function of the solar cell. Similarly, the preparation method of the solar cell is also only some non-limiting implementation methods provided by the present invention, and does not constitute a limitation on the execution subject or execution order of each step in the preparation method of these solar cells.

[0030] Specifically, first, the solar cell preparation equipment can place the substrate in an ultrasonic cleaning device, and use detergent-free water, deionized water, and ethanol to clean the substrate in sequence, wherein each step takes 20 minutes. Then, the substrate is subjected to ultraviolet ozone cleaning treatment via an ultraviolet ozone cleaning device, wherein the ultraviolet ozone cleaning treatment takes 20 minutes. Here, the base layer, also referred to as a substrate, can be FTO glass, ITO glass, or a flexible ITO conductive substrate.

[0031] Afterwards, the solar cell preparation equipment further prepares a self-assembled monolayer. The self-assembled monolayer material with a concentration of 0.3 mg / ml to 1 mg / ml is spin-coated on the substrate, wherein the spin-coating speed is 1500 rpm to 3000 rpm, the spin-coating time is 15 s to 30 s, the annealing temperature for preparing the hole transport layer is 80°C to 100°C, and the annealing time is 10 min to 20 min. Here, the material of the self-assembled monolayer includes at least one of 2PACZ, 4PACZ and Me-4PACZ.

[0032] Please refer to Figure 2 , Figure 2 A schematic flow chart of a method for preparing a solar cell according to some embodiments of the present invention is shown.

[0033] like Figure 2 As shown, according to the method for preparing a solar cell provided by the first aspect of the present invention, step S1 may be first performed: dissolving a urea-based compound in a solvent to obtain an interface modification precursor solution.

[0034] The solvent may be at least one of ethanol and isopropanol, and the urea-based compound includes hydroxyurea, and the concentration thereof is 1 mg / ml to 1.8 mg / ml.

[0035] Afterwards, the solar cell preparation device can perform step S2: spin-coating the interface modification precursor solution on the self-assembled monolayer to form an interface modification layer on the self-assembled monolayer to improve its carrier transport performance.

[0036] Specifically, the preparation equipment of the solar cell can be based on a one-step spin coating method to spin coat the interface modification precursor solution on the self-assembled monolayer, wherein the spin coating speed is 1500rpm~3000rpm, the spin coating time is 15s~30s, and can be preferably set to 20s. The annealing temperature for preparing the interface modification layer is 80℃~100℃, and the annealing time is 10min~20min.

[0037] Thereafter, the solar cell preparation device may perform step S3: sequentially preparing a perovskite light absorption layer, an electron transport layer, a hole blocking layer and a metal electrode on the interface modification layer.

[0038] Specifically, in the process of preparing the perovskite light absorbing layer, the solar cell preparation equipment can first dissolve the perovskite light absorbing layer precursor in an organic solvent to obtain a perovskite precursor solution. Here, the perovskite precursor includes at least one of FAMAPbI, FACsPbI, and FAMACsPbI. The organic solvent is a mixture of DMF and DMSO, and the volume ratio thereof is 3:1 to 5:1, or the organic solvent is a mixture of GBL and NMP, and the volume ratio thereof is 3:1 to 5:1.

[0039] Afterwards, the perovskite precursor solution is spin-coated on the surface of the interface modification layer to prepare the perovskite light absorption layer. Specifically, the solar cell preparation equipment can apply the perovskite precursor to the surface of the hole transport layer by slit coating, and then heat and anneal to obtain the perovskite light absorption layer. Among them, the annealing temperature for preparing the perovskite light absorption layer is 100℃~150℃, the annealing time is 15min~35min, and the air humidity can be 10%~15%.

[0040] Then, an electron transport layer, a hole blocking layer and a metal electrode are sequentially deposited on the surface of the perovskite light absorption layer. Here, the material of the electron transport layer can be C 60 Or PCBM, the material of the hole blocking layer can be BCP, and the thickness of the deposited metal electrode can be 60nm to 80nm.

[0041] Please refer to Table 1, which shows the experimental results of the embodiments and comparative examples under different preparation conditions.

[0042] Table 1 Comparison of experimental results of embodiments and comparative examples

[0043] <![CDATA[Jsc(mA / cm 2 )]]> Voc(V) FF(%) PCE(%) Example 1 26.42 1.16 81.3 24.91 Example 2 26.11 1.15 79.6 23.9 Example 3 25.93 1.14 79.4 23.47 Comparative Example 1 25.40 1.14 78.4 22.7 Comparative Example 2 25.35 1.13 78.6 22.5 Comparative Example 3 25.66 1.14 79.1 23.13

[0044] This experiment uses a solar cell prepared by the following specific method as Example 1. Those skilled in the art can understand that in order to verify the effect of the interface modification layer in this application, the following Comparative Examples 1 to 3 only control variables in the "preparation of the interface modification layer" to obtain comparative experimental results.

[0045] Embodiment 1:

[0046] Step 100: Cleaning the FTO (fluorine-doped SnO2 conductive glass) substrate;

[0047] Step 101: placing the FTO substrate in an ultrasonic cleaning device, and cleaning the FTO substrate in steps with detergent-free water, deionized water, and ethanol, each step lasting 20 minutes, and drying the substrate for use;

[0048] Step 102: treating the ultrasonically treated FTO substrate with UV-zone for 20 min;

[0049] Step 200: Preparation of a hole transport layer;

[0050] Step 201: Spin coating a clean substrate with a concentration of 0.5 mg / ml of 4PACZ at a spin coating speed of 3000 rpm for 20 seconds;

[0051] Step 202: annealing the obtained SAM layer at 80-100° C. for 10 min;

[0052] Step 300: Preparation of an interface modification layer;

[0053] Step 301: Dissolve 1.4 mg of hydroxyurea in 1 ml of ethanol solution for later use;

[0054] Step 302: Spin-coat the prepared interface modification precursor onto the SAM substrate in step 202, and deposit the thin film using a one-step spin coating method, with a spin coating speed and time of 3000 rpm and 20 s;

[0055] Step 400: Preparation of an absorption layer;

[0056] Step 401: dissolve 1.5 mol of FA0.85Cs0.15PbI3 perovskite solution in 1 ml of a solvent having a volume ratio of DMF:NMP=4:1, and stir for 2 hours for standby use, thereby obtaining a perovskite precursor;

[0057] Step 402: Spin-coat the reserved perovskite precursor onto the ETL substrate in step 202, and deposit the thin film using a one-step spin coating method, with a spin coating speed and time of 5000 rpm for 30 seconds;

[0058] Step 403: 5 seconds before the end of the spin coating deposition, 300 μL of anisole is quickly added dropwise to obtain a perovskite wet film;

[0059] Step 404: annealing the perovskite wet film obtained in step 403 at 150° C. for 10 min to obtain a perovskite dry film;

[0060] Step 500: preparing an electron transport layer;

[0061] Step 501: On the prepared perovskite film Evaporation 30nmC 60 ;

[0062] Step 600: preparing a hole blocking layer;

[0063] Step 601: On the prepared electron transport layer Evaporation of 6nm BCP;

[0064] Step 700: preparing a metal electrode;

[0065] Step 701: The film treated in step 501 is subjected to thermal evaporation to form a gold film, and a 110 nm thick silver electrode is evaporated.

[0066] Here, the concentration of hydroxyurea in Example 1 is 1.4 mg / ml, the concentration of hydroxyurea in Example 2 is 1 mg / ml, and the concentration of hydroxyurea in Example 3 is 1.8 mg / ml.

[0067] The comparative examples include solutions with too high or too low concentrations and without an interface modification layer. Specifically, comparative example 1 is a solar cell without the interface modification layer; the concentration of hydroxyurea in comparative example 2 is 2.2 mg / ml, and the concentration of hydroxyurea in comparative example 3 is 0.6 mg / ml.

[0068] It can be seen that when the concentration is 1.4 mg / ml, the efficiency of the device is the best. When the concentration is small, the wettability may not be significantly improved, resulting in poor device performance. When the concentration is too high, too much hydroxyurea may react with perovskite, resulting in poor device performance.

[0069] In summary, the solar cell and the method for preparing the solar cell provided by the present invention can be used to improve the unfavorable phenomenon of uneven coverage of the perovskite film due to the hydrophobicity of the SAM material, thereby improving the carrier transport performance at the interface, thereby improving the performance of the device.

[0070] Although the above methods are illustrated and described as a series of actions for simplicity of explanation, it should be understood and appreciated that these methods are not limited by the order of the actions, because according to one or more embodiments, some actions may occur in a different order and / or concurrently with other actions from those illustrated and described herein or not illustrated and described herein but understandable to those skilled in the art.

[0071] The previous description of the disclosure is provided to enable any person skilled in the art to make or use the disclosure. Various modifications to the disclosure will be apparent to those skilled in the art, and the general principles defined herein may be applied to other variations without departing from the spirit or scope of the disclosure. Thus, the disclosure is not intended to be limited to the examples and designs described herein, but should be granted the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a solar cell, characterized in that: The following steps are involved: dissolving the urea-based compound in a solvent to obtain an interface modification precursor solution; Spin coating the interface modification precursor solution on the self-assembled monolayer to form an interface modification layer on the self-assembled monolayer to improve its carrier transport performance; as well as A perovskite light absorption layer, an electron transport layer, a hole blocking layer and a metal electrode are sequentially prepared on the interface modification layer.

2. The preparation method according to claim 1, characterized in that The solvent is at least one of ethanol and isopropanol, the urea-based compound includes hydroxyurea, and the concentration thereof is 1 mg / ml to 1.8 mg / ml, and / or The annealing temperature for preparing the interface modification layer is 80° C. to 100° C., and the annealing time is 10 min to 15 min.

3. The preparation method according to claim 1, characterized in that: Based on a one-step spin coating method, the interface modification precursor solution is spin coated on the self-assembled monolayer, wherein the spin coating speed is 1500 rpm to 3000 rpm and the spin coating time is 15 s to 30 s.

4. The preparation method according to claim 1, characterized in that: The material of the self-assembled monolayer includes at least one of 2PACZ, 4PACZ and Me-4PACZ.

5. The preparation method according to claim 4, characterized in that: The steps of preparing the self-assembled monolayer include: A self-assembled monomolecular material with a concentration of 0.3 mg / ml to 1 mg / ml is spin-coated on a substrate, wherein the spin-coating speed is 1500 rpm to 3000 rpm, the spin-coating time is 15 s to 30 s, the annealing temperature for preparing the self-assembled monomolecular material is 80° C. to 100° C., and the annealing time is 10 min to 20 min.

6. The preparation method according to claim 5, characterized in that: The substrate is FTO glass, ITO glass or a flexible ITO conductive substrate. Before preparing the self-assembled monolayer, the preparation method further comprises the following steps: Placing the substrate in an ultrasonic cleaning device, and sequentially cleaning the substrate with detergent-free water, deionized water, and ethanol, wherein each step takes 10 to 20 minutes; and The substrate is subjected to ultraviolet ozone cleaning treatment by ultraviolet ozone cleaning equipment, wherein the ultraviolet ozone cleaning treatment lasts for 10 minutes to 20 minutes.

7. The preparation method according to claim 1, characterized in that: After forming the interface modification layer, the preparation method further comprises the following steps: dissolving a perovskite light absorbing layer precursor in an organic solvent to obtain a perovskite precursor solution; Spin-coating the perovskite precursor solution on the surface of the interface modification layer to prepare the perovskite light absorbing layer, wherein the annealing temperature for preparing the perovskite light absorbing layer is 100° C. to 150° C., and the annealing time is 15 min to 35 min; and The electron transport layer, the hole blocking layer and the metal electrode are sequentially deposited on the surface of the perovskite light absorbing layer.

8. The preparation method according to claim 7, characterized in that: The perovskite precursor includes at least one of FAMAPbI, FACsPbI, and FAMACsPbI, The organic solvent is a mixture of DMF and DMSO in a volume ratio of 3:1 to 5:1, or the organic solvent is a mixture of GBL and NMP in a volume ratio of 3:1 to 5:

1.

9. The preparation method according to claim 7, characterized in that: The material of the electron transport layer is C 60 Or PCBM, the material of the hole blocking layer is BCP, and the thickness of the deposited metal electrode is 60nm-80nm.

10. A solar cell, characterized in that: The solar cell is prepared by the method for preparing a solar cell according to any one of claims 1 to 9.